2010
DOI: 10.1007/s00468-010-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotopes in tree rings indicate improved water use efficiency and drought responses of a tropical dry forest tree species

Abstract: Understanding the responses of tropical trees to increasing [CO 2 ] and climate change is important as tropical forests play an important role in carbon and hydrological cycles. We used stable carbon isotopes (d 13 C) in tree rings to study the physiological responses of a tropical dry forest tree species in southern Mexico, Mimosa acantholoba to changes in atmospheric [CO 2 ] and variation in climate. Based on annual records of tree ring d 13 C, we calculated intrinsic water use efficiency (W i ) and interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
62
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 57 publications
12
62
1
4
Order By: Relevance
“…Mimosa acantholoba, a Mexican dry forest species, showed a 40% increase in iWUE over the past 40 years. However, no increase in C i was observed for this species (Brienen et al 2010b). Nock et al (2010) showed, similarly, an increase in iWUE for three tropical tree species from Thailand.…”
Section: Fluctuations In Growing Conditions and Physiological Responsmentioning
confidence: 69%
See 2 more Smart Citations
“…Mimosa acantholoba, a Mexican dry forest species, showed a 40% increase in iWUE over the past 40 years. However, no increase in C i was observed for this species (Brienen et al 2010b). Nock et al (2010) showed, similarly, an increase in iWUE for three tropical tree species from Thailand.…”
Section: Fluctuations In Growing Conditions and Physiological Responsmentioning
confidence: 69%
“…For ten tropical tree species long-term trends in stable isotope levels have now been obtained (Hietz et al 2005;Gebrekirstos et al 2009;Nock et al 2010;Brienen et al 2010b;Gebrekirstos et al 2010). A decrease in d 13 C over time was reported, which led to an increase in intrinsic water use efficiency (iWUE) for six species (Hietz et al 2005;Nock et al 2010;Brienen et al 2010b). Cedrela odorata and Swietenia macrophylla from Brazil showed an increase in C i over time, which led to an increase in iWUE of 34 and 52%, respectively, from 1850 to 1990 (Hietz et al 2005).…”
Section: Fluctuations In Growing Conditions and Physiological Responsmentioning
confidence: 95%
See 1 more Smart Citation
“…Brienen et al, 2011;Cernusak et al, 2007;Fichtler et al, 2010;Gebrekirstos et al, 2009;Hietz et al, 2005;Nock et al, 2011). …”
unclassified
“…Annual rings allow recovery of information on growth with precision and help to understand the dynamics of growth in relation to seasonality. In dry tropical regions several studies show a positive correlation between growth and precipitation (BRIENEN et al, 2011;ENQUIST;LEFFLER, 2001;FICHTLER et al, 2004;SEITZ, 2008;SCHONGART et al, 2006;VOLLAND-VOIGT et al, 2011;WILS et al, 2011;WORBES et al, 2003). Many researchers also apply the ring-width data to calculate the intervals of cutting cycles of natural forest in the tropics (BRIENEN; ZUIDEMA, 2006;COURALET et al, 2005;MATTOS et al, 2010;SCHONGART, 2008).…”
Section: Introductionmentioning
confidence: 99%